2009
DOI: 10.4314/just.v29i2.46226
|View full text |Cite
|
Sign up to set email alerts
|

Drying Characteristics Of Cap And Stem Of Mushroom

Abstract: Thin-layer drying of cap and stem of mushroom was studied at temperatures of 40, 50 and 60°C. Drying took place in the falling rate period, and the drying behaviour was adequately described by the Page's equation. The activation energy values of cap and stem were determined to be 26.96 and 26.85 kJ/mol, respectively. The computed values of frequency factor k o for cap and stem were 4174 and 6247 h -1 , respectively. The higher k o value for stem implied lower resistance to diffusion of moisture and therefore r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…In Ghana and most parts of the world, drying remains one of the best alternatives of preprocessing this mushroom. Drying of different species of mushrooms have been reported in previous studies [8][9][10][11]. It is one of the oldest means of food preservation and is applicable to a wide range of food products including P.ostreatus strain EM-1 [12] .The principle behind drying according to Labuza and Altunakar [13] is primarily reduction of moisture to levels low enough to inhibit microbial growth and also slow down enzymatic and other biological reactions that may contribute to food spoilage.…”
Section: Introductionmentioning
confidence: 87%
“…In Ghana and most parts of the world, drying remains one of the best alternatives of preprocessing this mushroom. Drying of different species of mushrooms have been reported in previous studies [8][9][10][11]. It is one of the oldest means of food preservation and is applicable to a wide range of food products including P.ostreatus strain EM-1 [12] .The principle behind drying according to Labuza and Altunakar [13] is primarily reduction of moisture to levels low enough to inhibit microbial growth and also slow down enzymatic and other biological reactions that may contribute to food spoilage.…”
Section: Introductionmentioning
confidence: 87%
“…RMSE and χ 2 compare the diff erences between the predicted moisture ratios and the experimental moisture ratios, while percentage error (PE) compares the absolute diff erences between the predicted moisture contents and the experimental moisture contents throughout the drying period (16,17).…”
Section: Interpretation Of Drying Datamentioning
confidence: 99%
“…The predicted moisture ratio was compared to the experimental moisture ratio using RMSE and χ 2 as shown below (16,17).…”
Section: Interpretation Of Drying Datamentioning
confidence: 99%
“…Figure 3 shows the relationship between MC and time at different drying temperatures. It can be observed that as drying time increased, samples MC decreased [ 12 , 36 ]. The initial moisture content recorded for Kent, Keitt, Haden, and Palmer mangoes was in the range 73.21-78.47%, 76.53-83.07%, 81.55-84.60%, and 82.8-87.20%, respectively.…”
Section: Resultsmentioning
confidence: 99%